2019
DOI: 10.1021/acs.energyfuels.9b00780
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Fine Particle Emissions from the Use of Two Fischer–Tropsch Fuels in a CFM56-2C1 Commercial Aircraft Engine

Abstract: The fine particulate matter (PM) emissions from the use of two types of Fischer–Tropsch aviation fuels and their 50:50 blends with military JP-8 were quantified as part of the first Alternative Aviation Fuel Experiment (AAFEX). Measurements were made 30-m downstream of a CFM56-2C1 engine for PM mass and number, particle size distribution, black carbon (BC), and volatile PM (sulfate + organics) using selected online instrumentation. The PM number emission index (EIN) ranged from ∼2 × 1015 to 7 × 1016 particles/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 32 publications
1
19
0
1
Order By: Relevance
“…Aircraft jet engines release volatile and non-volatile particles which feature different aerosol dynamics, airborne transport range and exposure potential [6,7]. Lab and field studies with alternative jet fuel blends have demonstrated that jet fuels with an elevated hydrogen content (low amount of unsaturated hydrocarbons) show lower soot emissions than a regular reference Jet A-1 for the same engine [8][9][10][11][12]. However, in order to use SAF in aviation, compliance with sustainability criteria have to be monitored along the entire supply chain.…”
Section: Introductionmentioning
confidence: 99%
“…Aircraft jet engines release volatile and non-volatile particles which feature different aerosol dynamics, airborne transport range and exposure potential [6,7]. Lab and field studies with alternative jet fuel blends have demonstrated that jet fuels with an elevated hydrogen content (low amount of unsaturated hydrocarbons) show lower soot emissions than a regular reference Jet A-1 for the same engine [8][9][10][11][12]. However, in order to use SAF in aviation, compliance with sustainability criteria have to be monitored along the entire supply chain.…”
Section: Introductionmentioning
confidence: 99%
“…Nagyon fontos természetesen a hajtóművek hosszú élettartama, hogy minél kisebb költséggel üzemben tarthatók legyenek, amit napjainkban már igen fejlett digitális elektronikus szabályozó [1] és diagnosztikai rendszerek [20] biztosítanak. Ilyen megoldások mellett más eljárásokra is szükség van, hogy a gazdaságosságon túl további, például környezetvédelmi előírásoknak is megfeleljen az üzemeltetett légi jármű [10]. A gyártók évtizedes tapasztalataikat felhasználva egyre újabb égéstér-konstrukciókat hoznak létre, amelyek -ötvözve a modern anyagtechnológia fémmátrixos kerámia alapanyagaival -nagy mértékben képesek az egyre szigorodó feltételeket teljesíteni [11].…”
Section: Bevezetésunclassified
“…Other previous studies also reported that the mode diameters of particle number EIs generally ranged from ~10 to 20 nm under high engine thrust conditions (e.g., Kinsey, 2009;Yu et al, 2017Yu et al, , 2019). An exception is Kinsey et al (2019), who investigated the emission characteristics of a commercial gas turbine engine (CFM56-2C1) onboard a DC-8 with blending two types of fuels (military JP-8 and Fischer-Tropsch: FT) under various thrust conditions and ambient temperatures. The sulphur content of fuels for the FT-fuels were much lower than that for the JP-8 fuels.…”
Section: Size Distributions Of Total Particles For Take-off Plumesmentioning
confidence: 99%
“…A number of experiments have been performed at engine-test facilities and under real-world conditions to investigate gaseous and particulate emissions from aircraft equipped with turbofan engines, which are commonly used in civil aviation (e.g., Hagen et al, 1998;Petzold et al, 1999Petzold et al, , 2005Kärcher et al, 2000;Brock et al, 2000;Herndon et al, 2008;Westerdahl et al, 2008;Onasch et al, 2009;Kinsey, 2009;Timko et al, 2010;Lobo et al, 2015aLobo et al, , 2015bMoore et al, 2017aMoore et al, , 2017bKinsey et al, 2019;Yu et al, 2017Yu et al, , 2019Durdina et al, 2019). The key findings from the previous studies include the following two points.…”
Section: Introductionmentioning
confidence: 99%